Effect of different light sources and enamel preconditioning on color change, H2O2 penetration, and cytotoxicity in bleached teeth - Gonçalves, R. S. [UNESP]; Costa, C. A.S. [UNESP]; Soares, D. G.S. [UNESP]; Santos, Paulo Henrique dos [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Briso, André Luiz Fraga [UNESP] (Operative Dentistry, 2016)
This study evaluated the effects of acid etching of the enamel and the combination of different light sources (halogen light, light-emitting diodes [LEDs], and LED/Laser) and the bleaching product on color change, penetration of hydrogen peroxide (H2O2), and cytotoxicity over time. The color change (DE) and the amount of H2O2 that permeated the tooth tissue were analyzed using a spectrophotometer. Cell metabolism and morphology were evaluated using the methylthiazol tetrazolium assay and scanning electron microscopy, respectively. The DE values and H2O2 permeation were not significantly different under any of the experimental conditions. Tooth whitening significantly reduced cell metabolism, regardless of whether a light source was used. Preconditioning the enamel did not influence the cellular metabolism in any group. In conclusion, combining the bleaching product with different light sources and/or preconditioning the enamel resulted in few significant changes in color, transenamel and transdentinal pene-tration of H2O2, or cytotoxicity and cell morphology.